The Contemporary Perspectives on Using Spiritual Practices in the Clinical Psychologist` Work - Lazorko, Olha (Psychological Prospects Journal, 2018)
The article reviews the reference scientific research on the use of the spiritual knowledge and practice in the work of clinical psychologists and psychotherapists, as well as the definition and explication of the axiological and contemporary perspectives of the spiritual component in the model of care in clinical practice. Along with the deep, fundamental understanding of the essence of spirituality and spiritual development of the individual in a psychological paradigm, Ukrainian scholars practically do not find research that examines the applied aspects of the connection of spirituality and the clinical practice of helping people. In the field of scientific and applied clinical research, there is a revival of interest in this issue. Regarding clinical practice, health and human illness are considered within the framework of a biopsychosocial model as a concept of the unity of the soul and body. The spiritual paradigm in the field of mental health has a huge potential for the transformation of personality and society. The author highlights two ways of practical integration of spirituality and psychotherapy: an active inclusion in the therapy of the discussion of spiritual issues and the introduction of spiritual practices (meditation, yoga, prayer, the teaching of holy texts) for healing and transformation; a demonstration of the physician’s willingness to cooperate and discuss spiritual matters with the client, without the active initiation of the therapist and the expectation of this initiative from the client. In this regard, the practical problem is the lack of specially targeted studying and training aimed at acquiring the knowledge, skills and practices of clinical psychologists in the use and implementation of new and traditional methods and practices that would promote the client’s spiritual progress and improve the quality of his mental health.